Journal of Bangladesh College of Physicians and Surgeons: An Ongoing Journey of Quality, Remembering the Past, Glorifying the Present and Anchoring a Lightning Future - Mostafi, Mamun; Sarwar , SM Rahid (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not available J Bangladesh Coll Phys Surg 2022; 40: 1-2